Waste management practices in residential communities in Butuan City a foundation element for community planning and design development - Santos, Shirlyn Lee J.
Traditionally and ideally, the local authority has been the sole provider of waste services. The local government provides the entire constituent of the waste management system, from the infrastructure up to the daily operation of services as well as the provision of facilities. However, this assistance from the government weren?t sufficient for waste minimization. The study aspired to identify the difference of waste management practices of organic type residential communities and planned type residential communities in Butuan City as well as it intends to adapt the effectiveness of the waste management in Brgy. Hizon, Davao City and Municipality of Santo Tomas, Davao del Norte into the chosen locale of Butuan City, in order to achieve sustainability in the diverse type of community. Nevertheless, the study aimed to integrate and adapt the best waste management practices of the chosen model sites to the study area. The proponent chose four areas in Butuan City, two residential communities from organic type of community and two residential communities from planned type. Survey questionnaires were distributed and a series of interviews were conducted to be able to gather sufficient information from both communities? waste management practices. Moreover, the researcher has had visits on the model sites which are the Brgy. Hizon, Davao City and Municipality of Sto. Toams, Davao del Norte. The researcher performed interviews and direct observations on both vicinities, and had visited the Material Recovery Facility in both places. According to the result of the survey conducted, it shows that common notion of the residents in planned communities is to give the whole responsibility of managing their garbage to the waste management services offered by the city government of Butuan. Residents? in the chosen planned communities don?t care much about segregation given that the entire waste produced by each household are gathered and collected by the CENRO. As the researcher mull over with the data gathered, results have shown that planned subdivision has more effective disciplinary control compared to the organic communities.